Evaluation of Soil Stiffness Parameters for Bored Pile Analysis Using Finite Element Method and Load–Settlement Curves - Wawan Azwansyah; Roesyanto; Syiril Erwin Harahap (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Determining soil stiffness parameters is essential in bored pile analysis using the finite element method because they strongly influence deformation predictions. This study evaluates the stiffness parameters of the Hardening Soil constitutive model by validating numerical results against Static Load Test (SLT) load–settlement curves. Soil parameters were derived from field investigation data, laboratory testing, and empirical correlations, including c′ from Standard Penetration Test (SPT) values, ϕ′ from the plasticity index, Eoed and Eur from consolidation tests, and E50 from correlation with Eoed. Validation was performed using the Mean Absolute Percentage Error (MAPE) based on the gradients of the load–settlement curve during each loading phase. The results show that MAPE consistently decreased with increasing loading cycles and reached the highly accurate category (MAPE < 10%) in the final loading cycle. The gradient-based evaluation indicates that E50 does not fully represent the initial loading response, whereas Eoed and Eur adequately represent soil stiffness under higher stress levels and during the unloading–reloading phases. The proposed approach provides a more comprehensive framework for evaluating soil stiffness parameters in the Hardening Soil constitutive model than validation based only on total deformation.